Sosialisasi Pembelajaran Daring bagi Mahasiswa pada Masa Pandemi - Kusaimah; Pransisko, Frengki (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2024)
The COVID-19 pandemic has transformed the global education system, including in Indonesia, by requiring learning to be conducted online. STIH YPM organized socialization and training on online learning for students to enhance their understanding of online learning platforms, their advantages and disadvantages, and effective usage. This training aims to assist students in adapting to remote learning, ensuring they can continue attending lectures and academic seminars at both national and international levels. The results indicate that students gained better knowledge of various online learning platforms such as Zoom, Google Classroom, and Edmodo. Furthermore, this program raised awareness about the importance of digital literacy in the academic field. With this training, students are expected to become more active and independent in utilizing technology as an effective learning tool, even beyond the pandemic.